1991
DOI: 10.1149/1.2085947
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Residual Chlorides on Gas Sensing Characteristics of Tin Oxide Gas Sensors

Abstract: In an investigation on carbon monoxide sensors, the effect on electrical conductivity of residual chloride content of tin oxide materials have been studied to provide information relating to the sensitivity and selectivity in the detection of carbon monoxide. The starting material was a-stannic acid, precipitated in the reactidn between tin chloride and ammonia, which was calcined at 650~ for 2 h. The lower the chloride content of the original dried precipitate, the greater was the surface area and the greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Moreover, for this sintering temperature, the sampl prepared using the solution reduction method still exhibited a much more a ractive room-temperature hydrogen sensing capacity than the other one prepared using th impregnation method. Chlorine-containing precursors are frequently used to load noble metal nano-catalysts in many applications, while chlorine is generally known to have adverse effects on these nano-catalysts [37][38][39]. A post-treatment is mainly adopted to remove chlorine in the precursors effectively, and the thermal removal of chlorine from H 2 PtCl 6 can be expressed explicitly as [37,40,41]:…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, for this sintering temperature, the sampl prepared using the solution reduction method still exhibited a much more a ractive room-temperature hydrogen sensing capacity than the other one prepared using th impregnation method. Chlorine-containing precursors are frequently used to load noble metal nano-catalysts in many applications, while chlorine is generally known to have adverse effects on these nano-catalysts [37][38][39]. A post-treatment is mainly adopted to remove chlorine in the precursors effectively, and the thermal removal of chlorine from H 2 PtCl 6 can be expressed explicitly as [37,40,41]:…”
Section: Resultsmentioning
confidence: 99%
“…prepared SnO 2 films from organic tin tartrate solved in water/ethanol mixed solutions but still added a small amount of inorganic acids for stabilizing the precursor solutions. Apparently, the counterions and impurity ions existing in the sols are harmful for controlling film properties 21–23 . For example, using chloridate as precursor will lead to random, n ‐type doping in the final samples.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the counterions and impurity ions existing in the sols are harmful for controlling film properties. [21][22][23] For example, using chloridate as precursor will lead to random, n-type doping in the final samples. So, it is still a challenge to obtain high-quality SnO 2 films derived from highly pure sols with no counterions and a mild chemical property, i.e., a neutralized pH condition.…”
Section: Introductionmentioning
confidence: 99%
“…In the final sensing materials layers, there has been a minimal presence of impurities. Son et al have previously reported on the negative effect of impurities on the performance of sensing materials 37 . Synthesis methods are equally significant as concentration reagent and organic surfactant, temperature, and solvent media in determining the final crystallographic planes of the P-N heterojunction.…”
mentioning
confidence: 99%